“Seberang Bersatu” Community Forest Group’s Strategy in Rehabilitating Forests and Former Tin Mining Land - Safitri, Rahmadita (International Journal Labs, 2023)
Environmental damage due to tin mining that is not accompanied by environmental preservation in Juru Seberang Village, Belitung Regency, which causes loss of biodiversity and increases the vulnerability of coastal residents requires a strategy to strengthen Ecological Citizenship through rehabilitating forests and ex-tin mine forests and land, namely, by conducting socialization to the community in achieving the strategy of strengthening ecological citizenship. The results show that there are several inhibiting factors and supporting factors in the process of achieving strategies for strengthening Ecological Citizenship through the HKm group. Among these factors, the amount of assistance from various parties such as the Ministry of Maritime Affairs and Fisheries (KKP), Ministry of Environment and Forestry (KLHK), Peat and Mangrove Restoration Agency (BRGM), Regional Development Planning Agency, CSAR, BUMN, and so on is the most important factor. The community of the community has a strong belief in the community to always protect the environment and care more about the environment, and the community is the main source of support for the management of marine protected areas.